2015
DOI: 10.1161/circep.114.002554
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Ganglionated Plexi Ablation on Electrophysiological Characteristics and Neuron Remodeling in Target Atrial Tissues in a Canine Model

Abstract: Background-The long-term effects of ganglionated plexi ablation on electrophysiological characteristics and neuron remodeling in target atrial tissues remain unclear. Methods and Results-Dogs in group 1 (control, n=8) were not subjected to ganglionated plexi ablation and observed for 1 month, and dogs in groups 2 to 4 (ablation groups, n=8 each) underwent ablation of the right-sided ganglionated plexi and observed for 1, 6, and 12 months, respectively. Atrial electrophysiological characteristics were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
2
12
1
1
Order By: Relevance
“…In structurally normal animal hearts, acute EGPA retains sinoatrial and atrioventricular nodal functions, and does not increase the inducibility of ventricular arrhythmia . Recently, Mao et al and Wang et al investigated the long‐term effects of EGPA on atrial/ventricular electrophysiological properties and sinoatrial/atrioventricular node function in noninfarcted canines. Mao et al found that systematic EGPA significantly decreased atrial ERP, increased the inducibility of atrial tachyarrhythmias and the density of TH‐ and ChAT‐positive nerves in the atrium at an 8‐week follow‐up.…”
Section: Discussionmentioning
confidence: 89%
“…In structurally normal animal hearts, acute EGPA retains sinoatrial and atrioventricular nodal functions, and does not increase the inducibility of ventricular arrhythmia . Recently, Mao et al and Wang et al investigated the long‐term effects of EGPA on atrial/ventricular electrophysiological properties and sinoatrial/atrioventricular node function in noninfarcted canines. Mao et al found that systematic EGPA significantly decreased atrial ERP, increased the inducibility of atrial tachyarrhythmias and the density of TH‐ and ChAT‐positive nerves in the atrium at an 8‐week follow‐up.…”
Section: Discussionmentioning
confidence: 89%
“…25 Indeed, a recent clinical report detailed previously unrecognized focal firing sources in the left atrial appendage found in 27% of patients having repeat procedures whose AF was successfully ablated by targeting these sites. 26 (2) The unexpected increase in heart rate reported by Wang et al 1 and others 5 could be because of increased sympathetic innervation from the right stellate ganglion, which ordinarily connects to the sinus node via the anterior right GP. With the ablation of the latter, neural plasticity and nerve growth of the interganglionic nerve, which bypasses the GP 27 can directly affect the sinus node to cause the persistent increased heart rate.…”
Section: Article See P 1276mentioning
confidence: 99%
“…Assuming that there is no damage to nerve cell bodies, such as exist within the atrial neural network after major GP ablation, nerve sprouts can emerge from each parent axon, thereby increasing the total number of axons exceeding the number of parents. 24 The GP ablation studies of Wang et al 1 and the experimental and clinical studies of others have shown: (1) autonomic remodeling in the form of neural plasticity comes from Scherlag Editorial Based on X. Wang et alwithin the atrial neural network in the form of nerve sprouting, reversal of AERP prolongation and rotor and focal source origins of AF initiation and maintenance. 25 Indeed, a recent clinical report detailed previously unrecognized focal firing sources in the left atrial appendage found in 27% of patients having repeat procedures whose AF was successfully ablated by targeting these sites.…”
Section: Article See P 1276mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, AF was more inducible in the treatment group compared to the control group at 6 and 12 months. (Wang et al, 2015) A second study targeting the epicardial ganglionated plexi in dogs similarly showed an increase in atrial arrhythmias, which was attributed to an overall decrease in the atrial effective refractory period and hyper-reinnervation of both the sympathetic and parasympathetic nerves. (Mao et al, 2014) By contrast, the sinus node seems to have the capability to remodel electrically after AF ablation, and has shown the potential to improve to normal function.…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 99%